A Novel Molten Oxide Fuel Cell Concept. Issue 3 (29th April 2016) - Belousov, V. V.; Fedorov, S. V.
Abstract: We suggest a novel molten oxide fuel cell (MOFC) concept. The MOFC is based on the oxygen‐ion‐conducting solid/molten oxide electrolyte (so‐called liquid‐channel‐grain‐boundary‐structure, LGBS, material) consisting of TeO2 solid grains and chemically compatible TeO2 +Te4 Bi2 O11 liquid electrolyte at the grain boundaries. The intergranular liquid channels provide the LGBS mechanical plasticity (ductility), which makes it easy to shape and alleviates problems due to thermal incompatibility with electrodes (CTE), and high ionic conductivity. The volume fraction of liquid varied from 0.15 to 0.17 at 600–640 °C. The cell performance has been examined by standard electrochemical methods. With air used as a cathode gas, the single cell showed the power 11.5 mW cm −2 at the current density 90 mA cm −2, electrolyte thickness 2.5 mm, and temperature 640 °C.